Labor Supply Preferences, Hours Constraints, and Hours-Wage Trade-offs - Altonji, Joseph G.; Paxson, Christina H. (Journal of Labor Economics, 1988)
In a labor market with tied hours-wage packages and wage dispersion for a particular type of job, constrained workers may be willing to sacrifice wage gains for better hours when changing jobs. Likewise, workers may accept jobs offering undesirable hours only if the associated wage gains are large. We investigate this issue empirically by examining whether overemployment and underemployment on the initial and new job affects the relation between hours changes and wage changes for quitters. Our results generally support the view that an individual requires compensation to work in a job that, given the individual's particular preferences, offers unattractive hours.